2013
DOI: 10.1007/s13311-013-0177-6
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Depletion Syndromes: Review and Updates of Genetic Basis, Manifestations, and Therapeutic Options

Abstract: Mitochondrial DNA (mtDNA) depletion syndromes (MDS) are a genetically and clinically heterogeneous group of autosomal recessive disorders that are characterized by a severe reduction in mtDNA content leading to impaired energy production in affected tissues and organs. MDS are due to defects in mtDNA maintenance caused by mutations in nuclear genes that function in either mitochondrial nucleotide synthesis (TK2, SUCLA2,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
271
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(277 citation statements)
references
References 135 publications
(199 reference statements)
5
271
0
1
Order By: Relevance
“…In this study, with whole-exome sequencing, we did not identify pathogenic mutations in any of the known mtDNA maintenance genes (El-Hattab and Scaglia 2013;Suomalainen and Isohanni 2010) to disclose the genetic aetiology of the disease in Patients 1 and 2, but further studies are ongoing to evaluate the role of the candidate genes identified by whole-exome sequencing (unpublished data provided by Dr. Javad Nadaf, Dr. Somayyeh Fahiminiya and Prof. Jacek Majewski, Department of Human Genetics, McGill University and Genome Quebec Innovation Center, Montreal, Canada) associated with these novel MDDS phenotypes. Most single mtDNA deletions are thought to be sporadic and thus not genetically transmitted (Chinnery et al 2004), but multiple mtDNA deletions can be inherited as an autosomal dominant or recessive trait (Zeviani et al 1990;Nishino et al 1999).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In this study, with whole-exome sequencing, we did not identify pathogenic mutations in any of the known mtDNA maintenance genes (El-Hattab and Scaglia 2013;Suomalainen and Isohanni 2010) to disclose the genetic aetiology of the disease in Patients 1 and 2, but further studies are ongoing to evaluate the role of the candidate genes identified by whole-exome sequencing (unpublished data provided by Dr. Javad Nadaf, Dr. Somayyeh Fahiminiya and Prof. Jacek Majewski, Department of Human Genetics, McGill University and Genome Quebec Innovation Center, Montreal, Canada) associated with these novel MDDS phenotypes. Most single mtDNA deletions are thought to be sporadic and thus not genetically transmitted (Chinnery et al 2004), but multiple mtDNA deletions can be inherited as an autosomal dominant or recessive trait (Zeviani et al 1990;Nishino et al 1999).…”
Section: Discussionmentioning
confidence: 94%
“…However, measuring intracellular mtDNA content is technically challenging and the amount of mtDNA is age-and tissue-related (Dimmock et al 2010;Morten et al 2007). Numerous pathogenic mutations have been found in the 12 nuclear genes responsible for encoding proteins vital to mtDNA maintenance (El-Hattab and Scaglia 2013;Suomalainen and Isohanni 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Genes associated with MDS encode proteins involved in maintenance of the mitochondrial nucleotide pool or in mtDNA replication (Copeland 2012;El-Hattab and Scaglia 2013), as observed for chromosome 10 open reading frame 2 (C10Orf2), also called Twinkle.…”
Section: Introductionmentioning
confidence: 99%
“…Located on chromosome 2, MPV17 encodes an inner membrane-associated mitochondrial protein of unclear function (El-Hattab and Scaglia 2013). Mutations in MPV17 are known to cause Navajo neurohepatopathy (OMIM #256810), a recessive, rapidly progressive mitochondrial DNA depletion syndrome of liver failure and neurologic deterioration with onset in the first year of life (Karadimas et al 2006;El-Hattab et al 2010;AlSaman et al 2012).…”
mentioning
confidence: 99%